Chronic Health Risks in Commercial Fishermen: A Cross-Sectional Analysis from a Small Rural Fishing Village in Alaska. Issue 2 (3rd April 2018) - Eckert, Carly; Baker, Torie; Cherry, Debra
ABSTRACT: Objectives : The purpose of this study is to evaluate chronic health risks before and during the fishing season in a sample of commercial fishermen, addressing the NIOSH priority of Total Worker Health TM . Methods : Gillnet license holders in Cordova, Alaska ( n  = 607) were contacted to participate in a preseason survey (March 2015) assessing health behaviors. A mid-season survey (July 2015) was also conducted. Physical exams and additional assessments were performed on a subset of these fishermen. Results : Sixty-six fishermen participated in the preseason survey and 38 participated in the mid-season survey. The study population was overwhelmingly white males with an average age of 49. The average BMI was 27 with 70% of the participants overweight or obese. Nearly 80% of the sample considered their health good or better. Participants reported longer working hours, less sleep, and less aerobic exercise during the fishing season ( P  < .05). FitBit TM monitoring ( n  = 8) confirmed less sleep and fewer steps during fishing season. In one exam ( n  = 20), 80% of participants showed measured hearing loss at 4 kz (conversation range), and 70% had one or more upper extremity disorders, including 40% with rotator cuff tendonitis. Conclusions : The prevalence of hearing loss, upper extremity disorders, and sleep apnea risk factors were higher than in the general population both before and during the fishing season. Occupational factors including exposure to noise, the upper extremity demands of gillnetting, and long working hours while fishing exacerbate these chronic health conditions. Health promotion programs targeted toward these conditions may present opportunities for improving total worker health.